Floral anatomy of Paepalanthoideae (Eriocaulaceae, Poales) and their nectariferous structures - Rosa, Michele Marcelino [UNESP]; Scatena, Vera Lucia [UNESP] (Oxford University Press (OUP), 2007)
• Background and Aims: Eriocaulaceae (Poales) is currently divided in two subfamilies: Eriocauloideae, which comprises two genera and Paepalanthoideae, with nine genera. The floral anatomy of Actinocephalus polyanthus, Leiothrix fluitans, Paepalanthus chlorocephalus, P. flaccidus and Rondonanthus roraimae was studied here. The flowers of these species of Paepalanthoideae are unisexual, and form capitulum-type inflorescences. Staminate and pistillate flowers are randomly distributed in the capitulum and develop centripetally. This work aims to establish a floral nomenclature for the Eriocaulaceae to provide more information about the taxonomy and phylogeny of the family. • Methods: Light microscopy, scanning electron microscopy and chemical tests were used to investigate the floral structures. • Key Results: Staminate and pistillate flowers are trimerous (except in P. flaccidus, which presents dimerous flowers), and the perianth of all species is differentiated into sepals and petals. Staminate flowers present an androecium with scale-like staminodes (not in R. roraimae) and fertile stamens, and nectariferous pistillodes. Pistillate flowers present scale-like staminodes (except for R. roraimae, which presents elongated and vascularized staminodes), and a gynoecium with a hollow style, ramified in stigmatic and nectariferous portions. • Conclusions: The scale-like staminodes present in the species of Paepalanthoideae indicate a probable reduction of the outer whorl of stamens present in species of Eriocauloideae. Among the Paepalanthoideae genera, Rondonanthus, which is probably basal, shows vascularized staminodes in their pistillate flowers. The occurrence of nectariferous pistillodes in staminate flowers and that of nectariferous portions of the style in pistillate flowers of Paepalanthoideae are emphasized as nectariferous structures in Eriocaulaceae. © The Author 2006. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.
Keywords: Eriocaulaceae; Floral anatomy; Monocotyledons; Nectariferous structures; Paepalanthoideae; Pistillate flowers; Poales; Staminate flowers; Staminodes; anatomy; angiosperm; flora; nectarivory; phylogeny; taxonomy; Actinocephalus; Leiothrix; Liliopsida; Paepalanthus; carbohydrate; classification; flower; histology; secretion; ultrastructure; Carbohydrates; Flowers; Phylogeny